Experience with teaching and applying process appraisals at a university. Issue 8 (27th July 2015) - De Man, Jozef; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract Software development mainly happens in small and very small enterprises. Establishing process improvement initiatives in such organizations is challenging because prevailing software improvement frameworks are perceived to be expensive and oriented towards larger companies. Much research has been done in adapting the standard frameworks to make them more suitable for small organizations. Lightweight techniques have been developed to reduce the cost of appraisals. In this paper, we report experience with teaching and applying a lightweight appraisal approach in a university context. Focus has been on educational aspects, but we believe that the approach can also be deployed in small and very small enterprises. Copyright © 2015 John Wiley & Sons, Ltd.